Analisis Pengendalian Kualitas untuk Mengurangi Cacat Produk 3D VR (Virtual Reality) Garment dengan Menggunakan Metode Six Sigma - Saroafifa Indriani; Yunita Primasanti; Erna Indriastiningsih (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Pan Brothers Tbk is one of the garment companies that adopted garment production in the form of 3D VR (Virtual Reality) as a garment prototype in Indonesia. In the process of making 3D VR products, many defective products must be revised. The study aims to implement the Six Sigma method and suggest improvements to reduce defects in 3D VR garment products using the Six Sigma method with the stages of defining, measuring, analyzing, improving, and controlling. In the define stage, the identification of the production process using the SIPOC diagram and identifying the type of defect. In the measure stage, the DPMO and sigma value calculations are carried out. The most defects are fitting not balanced and properly with a DPMO value of 269619.2 and a sigma value of 2.11. In the analysis stage with a fishbone diagram shows the factors that cause defects, namely man, machine, material, method, and environment. In the improvement stage, suggestions for improvements are given to reduce defects in 3D VR garment products. In the control stage, quality control is carried out by conducting internal training, upskilling, creating inspection report forms, adding teams to the QC division, and adding SOPs for the 3D VR producing process.